Clinical impact of radiofrequency ablation and stereotactic body radiation therapy for colorectal liver metastasis as local therapies for elderly, vulnerable patients. Issue 4 (20th March 2020) - Gotohda, Naoto; Nomura, Shogo; Doi, Manami; Karasawa, Katsuyuki; Ohki, Takamasa; Shimizu, Yasuhiro; Inaba, Yoshitaka; Takeda, Atsuya; Takaki, Haruyuki; Anai, Hiroshi; Ikeda, Masafumi; Sugimoto, Motokazu; et al.
Abstract: Background and Aim: Surgical resection is the standard local therapy for patients with colorectal liver metastases (CRLM). However, elderly and vulnerable patients sometimes have various organ dysfunctions. We have to conduct nonsurgical local therapies for those patients who might not tolerate surgery or systemic chemotherapy. Methods: We retrospectively reviewed medical records of 254 patients who underwent local therapies, including surgery, radiofrequency ablation (RFA), and stereotactic body radiation therapy (SBRT), for CRLM from January 2010 to December 2016, at seven tertiary‐care institutions in Japan. This study was designed to include elderly, vulnerable patients who received local therapy for CRLM. For those undergoing liver resection, only those having one or more points of the Charlson comorbidity index (CCI) were enrolled. Results: Of the total 169 enrolled patients, 122 patients underwent surgery, 42 RFA, and 5 SBRT as the first local therapy for CRLM. Median overall survival from the first local therapy was 5.9 years for the surgery group, 2.7 years for the RFA group, and 3.8 years for the SBRT group. The proportion of the patients with CCI ≧3 was significantly higher in the group of RFA/SBRT than surgery ( P  < 0.0001). In selected patients with CCI ≧3, there was no difference of the median survival time between the surgery group and the RFA group. Conclusions: We could have other treatment options to provide nonsurgical local therapies (RFA/SBRT) for elderly, vulnerable CRLM patients who have risks for surgery. Abstract : The number of elderly patients with colorectal liver metastasis (CRLM) is increasing. This article indicates the possibility of other treatment options to provide nonsurgical local therapies (radiofrequency ablation/stereotactic body radiation therapy) for elderly, vulnerable CRLM patients who have risks for surgery.